Study on the Breakdown Mechanism of Water Film on Corrugated Plate Wall Under the Horizontal Shear of Airflow: A Short Communication - Wang, Bo; Chen, Bowen; Ke, Bingzheng; Wang, Gongqing; Li, Ru; Wen, Jiming; Lu, Chuan; Tian, Ruifeng (Frontiers in Energy Research, 2020)
The corrugated plate dryer (CPD) is an important steam-water separation (SWS) equipment in the steam generator in the secondary loop of nuclear power plants (NPPs). Therefore, it is very important to understand the process and mechanism of liquid film rupture (LFR) on the wall surface of the CPD. In this paper, for the first time, the process of rupture of the liquid film (LF) on the surface of the corrugated plate is studied. The mechanism of LFR on the wall surface of a vertical corrugated plate was studied experimentally. A high-speed camera was used to collect the image of the broken liquid film, and an experimental research on the broken position, the broken process, and the broken shape of the liquid film was carried out. The results show that the rupture of the liquid film on the wall surface of the corrugated plate under the horizontal shear of airflow (HSA) mostly occurs at the upper middle position of the main flow of the liquid film. Also, the rupture position moves up with the increase in the Reynolds number of the liquid film. LFR needs to go through the process of stable flow, single strip-shaped liquid film (SSLF) detachment, two strip-shaped liquid film (TSSLF) formation, and finally chaotic disordered rupture. The angle between the two strip-shaped liquid films (ATSSLF) is positively related to the Reynolds number of the liquid film.